Tourism as a poverty alleviation strategy: opportunities and barriers for creating backward economic linkages in Lang Co, Vietnam : a thesis presented in partial fulfilment of requirements for the degree of Master of Philosophy in Development Studies at Massey University, New Zealand - Redman, David F. (Massey University, 2009)
This thesis looks at the potential for using tourism as a poverty alleviation strategy in the context of Vietnam and the Greater Mekong Subregion (GMS). The theoretical basis for this research stems for the growing recognition within development rhetoric of the place of tourism as a key industry in many developing nations, and the formation of a Pro-Poor Tourism (PPT) approach. The fieldwork section of this thesis looks at the barriers and opportunities for those in the poorer communities of Lang Co, a small town on the cental east coast of Vietnam, to supply the burgeoning tourism industry with locally produced products that are compatible with their current livelihood strategies. Results show that there are many opportunities for the poor to benefit from the rapidly growing tourism industry in Vietnam and the region. There is a strong recognition of tourism in national and regional development strategies, there is a rich cultural, environmental and social context driving the tourism industry and there are several initiatives taking place, such as the Vietnamese National Tourism Law, which include many elements of pro-poor tourism principles. However, this thesis has found many barriers also prevent poorer people from benefiting from tourism. In the case of Lang Co, the poor were often limited in their ability to participate in the industry by debt and lack of access to credit, lack of education and training opportunities, a declining natural resource base and by a lack of awareness and participation in the planning of the tourism industry. More widely, the tourism industry is centrally driven and focused on high growth and large infrastructure type developments which in some cases conflict with the principles of PPT and the ability of people at the ground level to participate. This research highlights the complexity of attempting to use tourism as a poverty reduction strategy given the wide range of stakeholders involved and various levels involved the planning and implementation of the tourism industry. The potential applicability of a concept of pro-poor tourism in a rapidly changing context such as Vietnam is contingent of the ability of the poor to have influence on an industry which is having an increasing effect on their lives and livelihoods.
Keywords: Pro-poor tourism; Poverty reduction; Citizen participation; Fields of Research::350000 Commerce, Management, Tourism and Services::350500 Tourism